Comparative Analysis of Sleep Hygiene and Patterns among Adolescents in Two Russian Arctic Regions: A Pilot Study - Sergey N. Kolomeichuk; Lyudmila S. Korostovtseva; Artem V. Morozov; Michail V. Bochkarev; Yury V. Sviryaev; Dina A. Petrashova; Victoria V. Pozharskaya; Alexander A. Markov; Michail G. Poluektov; Denis G. Gubin (MDPI AG, 2024)
Purpose: The circumpolar habitat stands as one of the most vulnerable environments for human activity and health. The primary study objective was to compare sleep-related factors, light exposure, social cues, and potential confounding variables among schoolchildren residing in the European Arctic region from two settlements situated below and above the Polar Circle using validated self-reported questionnaires. Materials and Methods: We recruited 94 children aged 13-15 years (40.4% males), matched by sex and age, from public educational institutions in two circumpolar settlements located below (Kem', Republic of Karelia; 64.6 NL) and above the Polar Circle (Apatity, Murmansk Region; 67.3 NL). Participants completed several surveys, including the Pediatric Daytime Sleepiness Scale, the Insomnia Severity Index, the Adolescent Sleep Hygiene Scale, and the Munich ChronoType Questionnaire, to evaluate sleep parameters and chronotype. The χ2 test was used to test for differences between proportions. Linear regression and multiple regression models with co-factors were applied to assess the relationship between studied indicators. Results: A noteworthy increase in physical activity was observed in children residing in Kem' compared to those in Apatity. Children from Apatity showed higher alcohol consumption than their counterparts from Kem'. The overall rate of excessive daytime sleepiness in the sample was 17.1%. Moderate insomnia symptoms were reported in 18.4% of adolescents living in Kem' and in 25% of respondents living in Apatity, respectively. Notably, participants from Kem' attained higher academic scores and had longer exposure to sunlight on schooldays. On the other hand, children from Apatity tended to have later bedtimes and sleep-onset times on schooldays. According to the Munich ChronoType Questionnaire data, a reliance on alarm clocks on schooldays, and a higher Sleep Stability Factor based on the Adolescent Sleep Hygiene Scale. Discussion: Our study indicating that higher physical activity and longer sunlight exposure among Kem' children on schooldays are associated with earlier wake-up times during schooldays, earlier bedtime whole week, reduced dependence on alarm clocks, and higher academic achievements. The results of older schoolchildren differ from many works published previously in the USA, Argentina, and Japan, which could be explained by the season when the study was performed. Here, we observed a negative impact on school performance and sleep parameters in children living in high latitudes, namely in circumpolar regions. Conclusions: Our study points out that adolescents living above the Polar Circle tend to have sleep problems, e.g., late sleep-onset times, higher excessive daytime sleepiness, and insomnia-related symptoms, because of experiencing reduced exposure to natural light. Future research encompassing assessments across all four seasons will provide a more comprehensive understanding.